2009
DOI: 10.1038/ejcn.2009.129
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of animal products, their nutrient components and postmenopausal circulating steroid hormone concentrations

Abstract: Background/Objectives: Little is known about nutritional factors that influence circulating concentrations of steroid hormones, which are consistently associated with risk of breast cancer for postmenopausal women. We aimed to investigate the association between consumption of animal products and the plasma concentrations of steroid hormones and sex hormone-binding globulin (SHBG). Subjects/Methods: Cross-sectional analysis was conducted on plasma from 766 naturally postmenopausal women. We measured plasma con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
(48 reference statements)
0
34
2
4
Order By: Relevance
“…Also, cholesterol is a precursor for several androgens, and high cholesterol content in meat may influence DHEA-S production, but no studies have confirmed this. In a cross-sectional study of postmenopausal Australian women by Brinkman et al ., significant negative associations were observed between total red and fresh red meat consumption and circulating concentrations of sex-hormone binding globulin, but not with DHEA-S; none of the types of fat nor cholesterol intake were associated with sex hormones (36). Finally, low DHEA-S may indicate adrenal cortex dysfunction, and has been observed in people with cancer, CVD, Alzheimer’s disease, other age-related and immune function disorders (37).…”
Section: Discussionmentioning
confidence: 86%
“…Also, cholesterol is a precursor for several androgens, and high cholesterol content in meat may influence DHEA-S production, but no studies have confirmed this. In a cross-sectional study of postmenopausal Australian women by Brinkman et al ., significant negative associations were observed between total red and fresh red meat consumption and circulating concentrations of sex-hormone binding globulin, but not with DHEA-S; none of the types of fat nor cholesterol intake were associated with sex hormones (36). Finally, low DHEA-S may indicate adrenal cortex dysfunction, and has been observed in people with cancer, CVD, Alzheimer’s disease, other age-related and immune function disorders (37).…”
Section: Discussionmentioning
confidence: 86%
“…Exposure to meat-derived mutagens has also been observed to be significantly correlated with DNA adducts in breast tissue, potentially leading to unrepaired DNA damage and carcinogenesis (52). A cross-sectional analysis found mean plasma concentrations of sex hormone-binding globulin (SHBG) to be lower with higher intakes of total and fresh red meat (53). Lower SHBG levels correspond with increased bioavailability of estradiol (54, 55).…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the potential influence of food on estrogen levels in post-menopausal women is scarce. There are suggestions that a higher fiber [2] intake and adherence to the Mediterranean diet [3] may be associated with lower estradiol levels, while higher milk [4] intake may be associated with higher levels. In the Nurses’ Health Study, we previously found that the Alternate Healthy Eating Index (AHEI) was associated with lower levels of estradiol among overweight post-menopausal women [5].…”
Section: Introductionmentioning
confidence: 99%